Kemampuan Berpikir Kreatif Ditinjau dari Self Regulated Learning dengan Pendekatan Open-Ended Pada Model Pembelajaran Creative Problem Solving - Salahuddin Akbar Agus Panuntun Hsm; Mohammad Asikin; Budi Waluya; Zaenuri Zaenuri (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
The ability to think creatively is very important to be developed in students, especially when learning is starting to shift to blended learning where students are required to be able to organize portions and also how to learn independently, for this reason, students in this era need to grow their creative abilities to be able to keep up with educational developments. This study aims to conduct studies related to factors that can foster creative thinking skills. The research method used in this study is the SLR (Systematic Literture Review) method. Data collection is done by collecting similar research articles and limiting it to the topic of mathematical creative thinking skills. The articles used in this study were 20 articles with the topic of creative thinking skills. Based on the literature review, the most influencing factors in creative thinking skills are problem-based models and open-ended approaches. For this reason, using the CPS model with an open-ended approach will provide a model with a new alternative approach that can be tried to improve creative thinking skills.